Adaptasi dan Implementasi Prinsip-Prinsip Desain Pembelajaran Jarak Jauh Daring Oleh Calon Guru Matematika - Kristanto, Yosep Dwi; Sulistyani, Niluh; Utomo, Beni (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2023)
The design principles of online distance learning that have been developed in previous studies need to be investigated in the process of adaptation and implementation. The process provides important insights to refine these principles to make them more appropriate to the learning context. The purpose of this study was to determine the process of adaptation and implementation of online distance learning design principles by preservice mathematics teachers. The present study employed qualitative research which is based on the activity theory model. The results of this study reveal the challenges experienced by preservice mathematics teachers in adapting and implementing online distance learning design principles. In addition, this study also finds that the community around the preservice mathematics teachers has an important role in supporting them to design and implement online distance learning.